RFID based automatic tollgate collection - ChowdaryPolavarapu, Sushma; Kunduru, Umamaheswari; Hari Nallamala, Sri (International Journal of Engineering and Technology, 2018)
Automation within the transport system proved to be a remarkable investment inside the improvement of smart cities. ETC â€œElectronic Toll Collectionâ€ pursuits to cast off the holdup at toll gates by way of amassing toll fee electronically. Using this era we can reduce the congestion in tollbooths, in particular all through festive seasons while traffic has a tendency to be heavier than ordinary. The principle aim of this paper is to develop a conversation gadget to automate the vehicle access, go out toll series the usage of RF-Identification technology. Statistics can be without problems exchanged among the vehicle owners and toll management, thereby facilitating an extra effective toll collection by using decreasing traffic problems and abolishing feasible person made mistakes. Aurdino MEGA2560 microcontroller acts as the heart of the device. When any automobile passes thru the Toll Gate, the RFID tag, that's connected to the vehicle, receives scanned and an interrupt sign is dispatched to Aurdino from the RFID module. The microcontroller sends a signal to motor driver, GSM module and LED. On receiving the signal from Aurdino, LED turns from red to green because of this that the vehicle can pass thru the toll gate and the motor gets into movement via lifting the gate.